The Urgency of Enforcing Criminal Sanctions Against Perpetrators Waste Incineration - Angelina, Piramitha (CV. Publikasi Indonesia, 2024)
The global issue of various adverse impacts and dangerous risks due to mistakes in waste management is intensively echoed as a shared responsibility to be resolved. As the holder of the G20 presidency in 2022, Indonesia even raised the issue of sustainable waste management in the G20 forum. Therefore, legal research is important to study and provide solutions to these problems from the legal aspect, so that it is useful, not only at the regional and national levels, but also for the sustainability of life in all parts of the world. The purpose of this study is to find out the urgency of enforcing criminal sanctions listed in local regulations against waste incinerators in Kubu Raya Regency, West Kalimantan Province, Indonesia, reviewed from the relative theory as a criminal purpose. This research is a normative legal research, with a legislative approach and a theoretical approach. Based on the results of the research, there are two reasons for the urgency of enforcing criminal sanctions against the large number of waste incinerators in Kubu Raya Regency. First, it is reviewed from a general precaution in relative theory, which is to prevent everyone from becoming a perpetrator of waste burning. Second, it is reviewed from a special provision in relative theory, which is to prevent the perpetrators of burning waste who have been convicted from repeating their actions. Through criminal law enforcement, if general and special prevention are carried out optimally, it is hoped that the purpose of the regional regulation can be realized, namely to reduce the danger posed by sarnpah, especially burned waste, protect and improve the quality of public health and the environment, and change community behavior in waste management.